2021
DOI: 10.1111/hsc.13345
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the family at the end‐of‐life: An ethnographic study on the role of food and eating practices for families facing death in Portugal

Abstract: Little has been said about the disruptive impact that the inability to eat and to participate in mealtimes has for patients with a life-threatening illness and their families.The aim of the current study is to overcome this gap and shed light on how food and eating practices are experienced by families at the end-of-life. An ethnographic research was developed in two Portuguese palliative care units: participant observation was conducted during 10 months and in-depth interviews were carried out with 10 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For patients during their illness trajectory, mealtimes and eating deficiencies are more than nutrients and encompass daily life with food preparation, social gatherings and interactions around mealtimes (Hilário & Augusto, 2021). Eating deficiencies add to consequences and stressors for patients with diminishing appetite and deteriorating conditions.…”
Section: Backg Roundmentioning
confidence: 99%
“…For patients during their illness trajectory, mealtimes and eating deficiencies are more than nutrients and encompass daily life with food preparation, social gatherings and interactions around mealtimes (Hilário & Augusto, 2021). Eating deficiencies add to consequences and stressors for patients with diminishing appetite and deteriorating conditions.…”
Section: Backg Roundmentioning
confidence: 99%
“…The three services in this study are focused on oral intake for older adults with swallowing/feeding difficulty at various stages, from prevention to the withdrawal of tube feeding. Oral intake means more than simply “adequate nutrition and hydration.“ The practices of oral intake involve the core identity of an individual at the personal and social levels [ 34 , 35 ] and are a symbolic act of family and patient relationships, especially at the end of life or during life-threatening illness [ 18 , 36 ]. Malnutrition in older adults is a major social problem in Western countries that is also straining healthcare expenditures, and in the United Kingdom, the NHS has developed guidance [ 37 ] and further education [ 38 ] for healthcare providers and caregivers with the aim of “adequate nutrition and hydration”.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, sociological approaches themselves have largely neglected the relevance of ‘family’ in the aftermath of death. Recent research has however shown the significance of ‘doing’ and ‘being’ ‘family’ at the end of life, in regard to the dying process itself (Almack, 2022; Almack et al, 2010; Borgstrom et al, 2019; Ellis, 2018; Hilário and Augusto, 2021) and the arranging and conducting of the funeral (Woodthorpe, 2017; Woodthorpe and Rumble, 2016). Beyond the funeral, Pearce and Komaromy (2021: 16–17) consider how family life is ‘done’ and made meaningful after a parental death; such issues may include the reconfiguration of roles and responsibilities, the construction or silencing of narratives of collective ‘family’ memories or loss of the very concept of ‘family’.…”
Section: ‘Family’ Sociology and The Aftermath Of Deathmentioning
confidence: 99%